Pengaruh Brand Equity dan Gaya Hidup Sehat terhadap Keputusan Pembelian Produk Plant-Based Meat Merek Meatless Kingdom - Pratiwi, Kusuma Ratna; Santoso, Siswanto Imam; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Plant-based meat is a vegetable process made with the texture, taste, and nutrition as similar to meat as possible. The plant-based meat focus in this study was focusing on the Meatless Kingdom brand. This study aims to analyze the influence of brand equity consisting of brand awareness, brand association, perceived quality, and brand loyalty as well as a healthy lifestyle on the decision to purchase plant-based meat products from Meatless Kingdom. This study was conducted from October 2024 to January 2025. The determination of the sample is purposively sampling, which is for consumers who have purchased the product at least once and are at least 17 years old. The number of samples was determined by Lemeshow's formula, which was 96 respondents. Primary data were obtained from questionnaires distributed online and secondary data were obtained from journal literature and books. This study used a case study method using a quantitative approach. Instrument tests were conducted on 32 respondents with a validity and reliability test. A normality test and a classical assumption test were conducted to test the regression model used. Analysis of data to determine the effect using multiple linear regression analysis which includes the coefficient of determination test, F test, and t test. The results of the study found that brand awareness, brand association, perceived quality, brand loyalty, and healthy lifestyle influenced the decision to purchase plant-based meat products from Meatless Kingdom both simultaneously and partially.